Assessing the Effectiveness of the Documentary Film Suster Apung in Enhancing Audience Interest in Documentary Viewing - Putra, Jaqualine Pramanta; Kasmir, Mursyid; Syarief, Fauzi; Susana, Susana (Sean Institute, 2025)
The documentary film Suster Apung tells the story of the struggle of a nurse serving in a remote area of Indonesia. This film highlights the dedication and sacrifice of medical personnel who face numerous challenges in delivering healthcare services to underserved communities. To effectively convey its message to the audience, a documentary must be supported by a well-constructed screenplay. A strong screenplay serves as a stimulus capable of eliciting immediate emotional responses from viewers. The quality of a documentary's screenplay can significantly enhance public empathy toward the individuals and communities portrayed. This study aims to examine the influence of the Suster Apung documentary’s screenplay on public empathy, using a sample of 130 randomly selected respondents. The research employs a quantitative approach with a descriptive-verificative method, analyzed using multiple linear regression. The findings indicate that cinematography, sound design, and the selection of interview subjects contribute 30.2% to the development of empathy, while the remaining 69.8% is influenced by other variables not examined in this study. The results suggest that the quality of a documentary's screenplay is shaped by effective cinematography, appropriate sound design, and relevant sources. The better the screenplay quality, the higher the potential for fostering audience empathy